Recent progress and future perspective of electron cryomicroscopy for structural life sciences. (18th February 2022) - Namba, Keiichi; Makino, Fumiaki
Abstract: The three-dimensional structure of biological macromolecules, such as proteins and nucleic acids, and their complexes is the fundamental information not only for life sciences but also for medical sciences and drug design. Electron cryomicroscopy has become an extremely powerful tool for high-resolution structural analysis of biological macromolecules, not just in addition to X-ray crystallography and nuclear magnetic resonance sepectroscopy (NMR) that have been used as the basic techniques in structural biology. By the development of hardware and software, such as transmission electron cryomicroscopes with highly stable and controllable electron optics, cold field emission gun and energy filter, complementary metal oxide semiconductor (CMOS)-based direct electron detectors with high frame rate and high sensitivity, high-speed computers and software programs for image analysis, electron cryomicroscopy now allows structure determination of biological macromolecules at atomic levels within a few days even from a drop of solution sample with an amount as small as a few micrograms. How can the structures of macromolecules be imaged and analyzed at atomic level resolution in their native states despite their high sensitivity to radiation damage at a relatively low level of electron irradiation? We describe recent progress and future perspective of electron cryomicroscopy for structural life sciences.